THE IMPORTANCE OF SWIMMING TECHNICS IN PHYSICAL DISABILITIES RECOVERY - Petrariu Ileana (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
This study aims primarily to determine the role that therapeutic swimming has in recovering the main physical impairment. The main functional impairments we have chosen are: kyphosis, lordosis and scoliosis. These deficiencies affect many people: children, young people, adults and even the elderly. The study includes 6 patients, 3 who were included in the experimental group and three included in the control group. Subjects within the experimental group were included in the water exercise recovery program and techniques specific to swimming therapy. They experienced markedly faster progress than those in the control group who followed only kinesiotherapy recovery therapy.